SPATIAL THINKING FOR INNOVATION: THE LEONARDO-MAXWELL-EINSTEIN METHOD, REVIVED - Rossler, Otto E. (European Scientific Journal, ESJ, 2013)
Free-running spatial intuition is like analog computation: it is indispensable for scientific progress despite its intrinsic inaccuracy. Do return to the first beginnings of a gold vein, was Maxwell’s advice. Returning to the gold vein of Einstein’s “happiest thought” leads to three other shiny results. Many accepted findings crumble as the barefoot method shows its mettle. A new cosmology is implicit and so is a new source of energy.